(untitled) (University Heart Journal, 2018)
Background: Repeated hospital readmissions are frequent and increasing over time in patients with heart failure (HF). The readmission rate within 3-6 months after discharge in these patients is 10-50%. Aim and Objective: This study was conducted to find out the demographic and socioeconomic factors contributing to readmission of patients with congestive heart failure admitted in university cardiac center of Bangabandhu Sheikh Mujib Medical University, Shahbag, Dhaka, Bangladesh during last quarter of 2016 and early quarter of 2017. Material and method: This was observational descriptive cross sectional study and enrolled 102 patients were enrolled for the study. Complete medical records were reviewed carefully. Results:A total of 68 men and 34 women with a mean (±SD) age of 55 (±14) years constitute the study population. Most of the population (42%) who belongs to age group 51-60 years had readmissions (p <0.0004). De-motivation due to negative comments from surrounding causing fully or partially drugs discontinuation (P <0.008) and poor adherence to drug (P <0.004) were associated with readmissions. Conclusion: After proper addressing of possible all medical factors and co morbidities, optimizing education strategies in a manner to respect the patients’ level of understanding; emphasizing the importance of medication adherence, diet and life style modification, increasing the self-monitoring skills as well as supporting the spouse and family members are considered as effective measures to reduce readmission rate due to congestive heart failure. University Heart Journal Vol. 12, No. 2, July 2016; 76-81